REPRESENTASI MAKNA FEMINISME PADA SAMPUL MAJALAH VOGUE VERSI ARABIA EDISI JUNI 2018 (Analisis Semiotika dengan Perspektif Roland Barthes) - Michael Jibrael Rorong; Diana Suci (SEMIOTIKA: Jurnal Komunikasi, 2019)
ABSTRACTThe representation of the meaning of feminism on the cover of the June 2018 edition of Vogue magazine is the theme of this study. The problem to be investigated is how the representation of the meaning of feminism and how the moral message contained in the cover of the Arabic version of Vogue magazine in the June 2018 edition. The author uses a qualitative method with Roland Barthes's semiotic analysis approach. The results of this study conclude that first, the representation of the meaning of feminism in the photos on the cover of the magazine using Roland Barthes's semiotics shows that the Saudi Arabian Royal family as shown by Princess Hayfa as her model, looks insensitive to the situation and conditions that actually occur in society in Arabia . The myth to be conveyed in the photo is that as an Arab who is not conservative and as a modern woman, Princess Hayfa is too unconcerned about her own religion and culture which is a long-held teaching by her ancestors in Saudi Arabia, even though she is a role model from the Royal family to its people in the country of Saudi Arabia. The second conclusion is the moral lessons that can be drawn from the phenomena found on the cover of the Arabic version of the Vogue magazine in the June 2018 edition, it is very important to preserve the noble values believed by the previous ancestors, bearing in mind that the cultural values were born from good Islamic teachings. and true based on the arguments in the Holy Qur'an and its hadiths. However the development of the times from time to time, as Muslims we are obliged to stick to the teachings of Islam that we believe from birth.Keywords: Magazine, Feminism, Semiotics, Roland Barthes Theory.ABSTRAKRepresentasi makna feminisme pada sampul majalah Vogue versi arabia edisi Juni 2018 merupakan tema dalam penelitian ini. Masalah yang ingin diteliti adalah bagaimana representasi makna feminisme dan bagaimana pesan moral yang terkandung pada sampul majalah Vogue versi Arabia edisi Juni 2018. Penulis menggunakan metode kualitatif dengan pendekatan analisis semiotika Roland Barthes. Hasil penelitian ini menyimpulkan bahwa pertama, representasi makna feminisme pada foto pada sampul majalah dengan menggunakan semiotika Roland Barthes menunjukkan bahwa pihak keluarga Kerajaan Arab Saudi sebagaimana ditampilkannya Putri Hayfa sebagai modelnya, terlihat tidak peka terhadap situasi dan kondisi yang ada sebenarnya yang terjadi pada masyarakat di Arab. Mitos yang hendak disampaikan pada foto itu adalah bahwa sebagai orang Arab yang tidak konservatif dan sebagai seorang wanita modern, Putri Hayfa terlalu kurang peduli terhadap agama dan kebudayaannya sendiri yang merupakan ajaran yang dianut sudah lama oleh para leluhurnya di Arab Saudi, padahal ia merupakan role model dari keluarga Kerajaan untuk masyarakatnya di negara Arab Saudi. Kesimpulan yang kedua yaitu pelajaran moral yang dapat dipetik dari fenomena yang ditemukan pada sampul majalah Vogue versi Arabia edisi Juni 2018 ini adalah sangat penting untuk menjaga nilai-nilai luhur yang diyakini oleh para leluhur terdahulu, mengingat nilai kebudayaan tersebut lahir dari ajaran Agama Islam yang baik dan benar berdasarkan dalil-dalil yang ada di kitab suci Al-Quran beserta hadist-hadistnya. Bagaimanapun perkembangan zaman dari masa ke masa, sebagai umat muslim kita berkewajiban tetap berpegang teguh pada ajaran Agama Islam yang kita yakini sejak lahir.Kata Kunci : Majalah, Feminisme, Semiotika, Teori Roland Barthes.